ANALISIS PENGARUH TEKNOLOGI KOMUNIKASI DAN PERUBAHAN PRILAKU - Hasdiyanto Hafied (JURNAL BADATI, 2024)
The aim of this research is the influence of the use of communication technology and how communication technology influences human behavior with current communication technology. The descriptive method used in this research produces descriptive data in the form of written or spoken words and observations of people's behavior. In this case, researchers talk to sources through interviews. The data obtained in the form of notes, archives and documents required as secondary data were then collected by researchers. The collected results were compiled thoroughly and methodically after undergoing qualitative analysis. Data triangulation was then used to verify the accuracy of the data. The advancement of information and communication technology is a trend that cannot be reversed. Many aspects of human life have progressed in the era of globalization. Therefore, general knowledge about this technology is necessary for society as a whole to transition into the era of globalization. Without ethics and understanding, it is difficult to utilize technology to improve people's lives.